Makna Work-Life Balance bagi Karyawan Shift: Studi Fenomenologi pada Pegawai PLN Nusantara Power UP (MNHS): Penelitian - Marssel Michael Sengkey; Nova Lisye Sinaulan; Zefanya Marchfirstio. Immanuel Bala; Christyo Erold. Jeremy Luhulima; Natalia Fabiola Kawung (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to understand the meaning of work-life balance from the subjective perspective of employees working in shift work systems at PT PLN Nusantara Power. Using a qualitative approach with a phenomenological method, this study explores the experiences of five shift workers through in-depth interviews. The research findings show that work-life balance for shift workers is uniquely and contextually defined, not just as a balanced division of time between work and personal life, but also as an effort to create emotional, physical, and social harmony amidst uncertain work schedules. Participants revealed the importance of family support, adaptability, and time management strategies as key to maintaining life balance. These findings have implications for the development of organizational policies that are more responsive to the needs and well-being of employees with non-conventional work systems.